Structural response of monoblock railway concrete sleepers and fastening systems subject to coupling vertical and lateral loads: A numerical study. (December 2021) - El–sayed, H.M.; Zohny, H.N.; Riad, H.S.; Fayed, M.N.
Abstract: Monoblock prestressed concrete sleepers are the most dominant type of sleepers in ballasted railway tracks. As such, it is important to provide optimized designs to the concrete sleepers and the associated fastening systems to ameliorate railway safety and to save both capital and maintenance funds. Therefore, a three-dimensional finite element railway model was created and verified. The response of both concrete sleepers and fastening components to coupling vertical and lateral loading was quantified. Such loading form typically occurs at horizontal railway sections causing damage to the railway track components. The influences of the sleeper spacing, elastic modulus of the rail pad, and friction coefficient at the contact surfaces of the rail and sleeper with the rail pad under varied lateral loadings were investigated. The interaction influence between parameters was thoroughly discussed. Among the studied parameters, the finite element model outcomes showed that the elastic modulus of the rail pad and the coefficient of friction are the most critical parameters with respect to the lateral load path and the local response of concrete sleeper and fastening system, especially at high lateral loadings. By using a relatively soft rail pad (elastic modulus = 100 MPa), the concrete material remained below the compressive and tensile fatigue limits even under high lateral loadings provided that the coefficient of friction remains limited to 0.3. By contrast, for a given lateral to vertical loading ratio, a continuous increase in the developed stresses of the concrete material and rail pad was detected as the elastic modulus changed from 100 MPa to 2000 MPa and the coefficient of friction increased from 0.3 to 0.9. The influence of sleeper spacing on the behaviour of railway tracks is only tangible on the distribution of the vertical wheel load. Lastly, the peak stress magnitudes of the ballast bed could be increased by 50% as the lateral to vertical loading ratio reached 0.6 compared to the case where the lateral load is absent. The experience gained from this article would help to formulate specific recommendations to improve the design of concrete sleepers, fastening systems, and ballast bed.